Surveillance of anti-tuberculosis drug resistance in the world: an updated analysis, 2007-2010 - Matteo Zignol; Wayne van Gemert; Dennis Falzon; Charalambos Sismanidis; Philippe Glaziou; Katherine Floyd; Mario Raviglione
OBJECTIVE: To present a global update of drug-resistant tuberculosis (TB) and explore trends in 1994-2010. METHODS: Data on drug resistance among new and previously treated TB patients, as reported by countries to the World Health Organization, were analysed. Such data are collected through surveys of a representative sample of TB patients or surveillance systems based on routine drug susceptibility testing. Associations between multidrug-resistant TB (MDR-TB) and human immunodeficiency virus (HIV) infection and sex were explored through logistic regression. FINDINGS: In 2007-2010, 80 countries and 8 territories reported surveillance data. MDR-TB among new and previously treated cases was highest in the Russian Federation (Murmansk oblast, 28.9%) and the Republic of Moldova (65.1%), respectively. In three former Soviet Union countries and South Africa, more than 10% of the cases of MDR-TB were extensively drug-resistant. Globally, in 1994 to 2010 multidrug resistance was observed in 3.4% (95% confidence interval, CI: 1.9-5.0) of all new TB cases and in 19.8% (95% CI: 14.4-25.1) of previously treated TB cases. No overall associations between MDR-TB and HIV infection (odds ratio, OR: 1.4; 95% CI: 0.7-3.0) or sex (OR: 1.1; 95% CI: 0.8-1.4) were found. Between 1994 and 2010, MDR-TB rates in the general population increased in Botswana, Peru, the Republic of Korea and declined in Estonia, Latvia and the United States of America. CONCLUSION: The highest global rates of MDR-TB ever reported were documented in 2009 and 2010. Trends in MDR-TB are still unclear in most settings. Better surveillance or survey data are required, especially from Africa and India.